2019
DOI: 10.1016/j.learninstruc.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the use of conceptually-derived strategies in arithmetic: using inversion problems to promote the use of associativity shortcuts

Abstract: Declarations of interest: None ACKNOWLEDGEMENTS: This work was supported by a PhD Studentship from Loughborough University Doctoral college. We would like to thank Jayne Pickering who helped to dual-score the data. C.G. is supported by a Royal Society Dorothy Hodgkin Fellowship. Highlights • Associativity is an arithmetic concept that children and adults struggle to apply • Inversion is a simpler concept that older children and adults easily apply • Solving inversion problems ('a + b-b') increased subsequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…Edwards (2013) found that self-reported shortcut use was significantly higher on 'a × b ÷ c' problems that were conducive to a shortcut than those that were not conducive. Eaves et al, (2019) found that self-reported users of the shortcut solved more conducive 'a + b -c' problems in a restricted timeframe than individuals who did not self-report using the shortcut, but that self-reported users and non-users did not differ on non-conducive 'a + b -c' problems. Comparing performance on conducive and non-conducive problems is therefore one way that researchers could investigate implicit associativity shortcut use independently from other concepts.…”
Section: Measurementmentioning
confidence: 80%
See 1 more Smart Citation
“…Edwards (2013) found that self-reported shortcut use was significantly higher on 'a × b ÷ c' problems that were conducive to a shortcut than those that were not conducive. Eaves et al, (2019) found that self-reported users of the shortcut solved more conducive 'a + b -c' problems in a restricted timeframe than individuals who did not self-report using the shortcut, but that self-reported users and non-users did not differ on non-conducive 'a + b -c' problems. Comparing performance on conducive and non-conducive problems is therefore one way that researchers could investigate implicit associativity shortcut use independently from other concepts.…”
Section: Measurementmentioning
confidence: 80%
“…Three studies have compared performance on conducive and non-conducive associativity problems (Eaves et al, 2019(Eaves et al, , 2020Edwards, 2013). Edwards (2013) found that self-reported shortcut use was significantly higher on 'a × b ÷ c' problems that were conducive to a shortcut than those that were not conducive.…”
Section: Measurementmentioning
confidence: 99%
“…Second, in a classroom intervention study with adults, Eaves et al (2019) found that individuals who solved “a + b − b” inversion problems were more likely than individuals who solved “a + b − a” inversion problems to subsequently use the associativity shortcut on “a + b − c” problems. They proposed two mechanisms through which “a + b − b” inversion problems helped individuals to identify the associativity shortcut.…”
Section: Introductionmentioning
confidence: 99%
“…Empirically, three strands of research provide some preliminary evidence that attention could be important for identifying associativity shortcuts (Dubé & Robinson, 2010; Eaves et al, 2019; Landy & Goldstone, 2007a). In the experimental studies by Landy and Goldstone (2007a, 2007b, 2010), adults validated the equivalence of multi-term problems and solved multi-term problems such as “2 + 3 × 4” in conditions where the spacing within and between the operations was manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple publications characterize the types of knowledge common to mathematics. Although there are many studies for students in regular education at primary and secondary education levels [20][21][22], very few can be found for higher education and adults [23,24]. Particularly limited is the number of publications in the Colombian context.…”
Section: Introductionmentioning
confidence: 99%